(untitled) (Quantum Frontiers Journal P-ISSN 3117-6070 and E-ISSN 3117-6089, 2025)
Quantum Key Distribution (QKD) provides information-theoretic security guaranteed by the laws of physics rather than computational hardness – making it the primary tool for quantum-secure communication against harvest-now-decrypt-later quantum threats. This paper proposes the Quantum Cryptographic Protocol Design and Analysis (QCPDA) framework, evaluating six quantum cryptographic protocols – BB84, E91, MDI-QKD, Twin-Field QKD (TF-QKD), Quantum Digital Signatures (QDS), and Quantum Secret Sharing (QSS) – across five dimensions: unconditional security, key generation rate, maximum secure distance, noise tolerance, and implementation complexity. TF-QKD achieves the longest secure distance (605 km on ultra-low-loss fibre) but lowest key rate. MDI-QKD eliminates all detector side-channels at moderate key rates. BB84 achieves the highest composite QCPDA score (8.24) due to commercial maturity. QCPDA provides a protocol selection guide mapping deployment scenarios (metropolitan, intercity, long-haul, multi-party) to optimal protocols, and discusses the complementary roles of QKD and NIST post-quantum cryptography standards for quantum-secure infrastructure.